2014
DOI: 10.1016/j.stemcr.2014.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Differentiation of Pluripotent Stem Cells into Osteoblasts Using Four Small Molecules under Serum-free and Feeder-free Conditions

Abstract: SummaryPluripotent stem cells are a promising tool for mechanistic studies of tissue development, drug screening, and cell-based therapies. Here, we report an effective and mass-producing strategy for the stepwise differentiation of mouse embryonic stem cells (mESCs) and mouse and human induced pluripotent stem cells (miPSCs and hiPSCs, respectively) into osteoblasts using four small molecules (CHIR99021 [CHIR], cyclopamine [Cyc], smoothened agonist [SAG], and a helioxanthin-derivative 4-(4-methoxyphenyl)pyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 35 publications
1
90
2
Order By: Relevance
“…We took advantage of the serum-free and feeder-free strategy for osteoblast induction that we reported in a 2D culture ( 14 ). Here, the mESCs maintained in the 3D culture were directly subjected to this strategy (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We took advantage of the serum-free and feeder-free strategy for osteoblast induction that we reported in a 2D culture ( 14 ). Here, the mESCs maintained in the 3D culture were directly subjected to this strategy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported an effective stepwise differentiation protocol for osteoblast differentiation from PSCs that uses four small-molecule inducers under serum-free and feeder-free conditions ( 14 ). However, this method was established under the conventional 2D culture.…”
Section: Introductionmentioning
confidence: 99%
“…used various small molecule inducers, such as SAG and TH under serum-free and feeder free conditions to create a stepwise differentiation protocol for osteoblast differentiation from pluripotent stem cells. 42 In this in vivo study, we used small molecule SAG together with NELL-1 protein to enhance bone healing in a critical-sized defect model.…”
Section: Discussionmentioning
confidence: 99%
“…Now that a number of groups have demonstrated differentiation of ESCs and induced pluripotent stem cells into skeletal cell types Phillips et al, 2001;zur Nieden et al, 2003;Sottile et al, 2003;Li and Niyibizi, 2012;Egusa et al, 2014; Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/diff Kanke et al, 2014;Trettner et al, 2014), research has shifted towards the identification of factors that can improve the output of these cell types, which remains insufficient in basic osteogenic medium. For example, we have recently demonstrated that the yield of chondrocytes within differentiated cultures can be increased to 57% simply through the continuous supplementation of culture with bone morphogenetic protein-2 (BMP-2) (zur Nieden et al, 2005).…”
Section: Introductionmentioning
confidence: 99%